Financial Literacy: Pengetahuan, Kepercayaan Diri dan Perilaku Keuangan Mahasiswa Akuntansi - Gilang Puspita; Isnalita Isnalita (Owner : Riset dan Jurnal Akuntansi, 2019)
The aims of this research is to examine the effect of financial knowledge and self confidence on financial behavior, the effect of self confidence on financial behavior, and the role of mediating self confidence on the relationship of financial knowledge to financial behavior. This research processed primary data using a questionnaire distributed to the student of Airlangga University. The research sample was selected using the Slovin formula at the level of confidence 5%. The sample analyzed were 328 questionnaire. The analytical tool used is Structural Equation Modeling with the Partial Least Square approach. The results showed that financial knowledge had an effect on self-confidence, self-confidence had an effect on financial behavior, self-confidence mediated the effect of financial knowledge on financial behavior. In addition, financial knowledge does not affect financial behavior.